On finite subject-to-object raising in Spanish - Herbeck, Peter (Borealis – An International Journal of Hispanic Linguistics, 2020)
In this paper, we analyze inflected complements of perceptive, causative and permissive verbs in which the null subject is obligatorily co-referent with the matrix object antecedent. Even though these configurations have mostly received a control or a ‘pseudo-relative’ analysis in Spanish, we argue that the structure is best explained by means of finite ‘subject-to-object’ raising, which has been proposed for languages like Greek, Romanian, Japanese or Korean. The analysis will be argued to capture several intriguing properties of this configuration which have been noted in the literature, such as temporal anaphoricity, direct perception readings, obligatory co-reference, floating quantifiers, emphatic pronouns, and resumptive pronoun strategies. We argue that left-peripheral as well as temporal deficiency of the embedded clause has the consequence that the CP is not a strong phase and cannot legitimate structural nominative case, making A-movement out of the inflected complement possible. Finally, we discuss some related structures that point to the conclusion that ‘finite raising’ exists in the full-fledged pro-drop language Spanish.